Cell-mediated autoimmunity in NZB mice - Stiller, C. R. (1973)
NZB mice spontaneously develop immune-complex nephritis comparable to that of human systemic lupus erythematosus in which the principal immunologic mechanism is thought to be humoral. A prominent histologic feature of lupus nephritis is round cell infiltration suggesting that cell-mediated immunity may also be important. Fibroblast monolayers from NZB and BALB/c (H-2 identical) embryos were cultured with spleen cells, using morphologic criteria to estimate monolayer damage. Cytotoxicity against autologous fibroblasts was demonstrated when spleen cells from older, diseased NZB mice were used. Cells from younger NZB mice, prior to development of renal disease, show cytotoxicity of intermediate degree. No significant cytotoxicity was demonstrable against BALB/c monolayers by the NZB cells. We interpret this as indicating the reactivity is not H-2 related. An interesting possibility is that it is a determinant on the ubiquitous viral particles seen.